2006
DOI: 10.1007/s10384-005-0281-1
|View full text |Cite
|
Sign up to set email alerts
|

Low Conversion Rate to Multiple Sclerosis in Idiopathic Optic Neuritis Patients in Taiwan

Abstract: Idiopathic ON patients in Taiwan have an older age at onset and a higher percentage of optic disc edema than reported in previous literature. The characteristic features of ON patients associated with a high risk of developing MS are female sex, retrobulbar type ON, CNS imaging abnormalities, elevated CSF IgG index, and recurrence. Idiopathic ON patients in Taiwan display a significantly lower conversion rate to MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
52
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 30 publications
(48 reference statements)
13
52
2
Order By: Relevance
“…We found that the mean annual incidence of MS in Taiwan was 0.085 per 1,000 persons, and the cumulative incidence (or cumulative probability) of MS conversion was 0.78% over the 5 years of our study. In Asian countries [10,23,25] , and in African populations [26] , the conversion rates are relatively low compared with those in Western countries. Both ethnic and regional factors may play a role in the wide range of MS conversion rates in various countries [27,28] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that the mean annual incidence of MS in Taiwan was 0.085 per 1,000 persons, and the cumulative incidence (or cumulative probability) of MS conversion was 0.78% over the 5 years of our study. In Asian countries [10,23,25] , and in African populations [26] , the conversion rates are relatively low compared with those in Western countries. Both ethnic and regional factors may play a role in the wide range of MS conversion rates in various countries [27,28] .…”
Section: Discussionmentioning
confidence: 99%
“…It can be the initial presentation of MS, or it can occur later in the course of the disease. However, the conversion percentage varies widely (6.5-75%) over an observational period of 3 years or longer [4,5,10,[22][23][24] . The wide range of conversion rates from different studies is probably due to differences in the lengths of follow-up and to the lack of uniform diagnostic criteria for MS. Another reason may be the low prevalence and incidence of MS in Taiwan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some factors are significantly predictors of secondary evolution of optic neuritis to multiple sclerosis (p<0.05), in particular: female sex, retrobulbar type of optic neuropathy, recurrence, elevation of the IgG index in cerebrospinal fluid and the existence of signal abnormalities in cerebral imaging [14]. The two year cumulative probability of secondary transformation from optic neuritis to multiple sclerosis is estimated to be 5.92% and that of five years to 14.28% [14].…”
Section: Discussionmentioning
confidence: 99%
“…The two year cumulative probability of secondary transformation from optic neuritis to multiple sclerosis is estimated to be 5.92% and that of five years to 14.28% [14].…”
Section: Discussionmentioning
confidence: 99%